Analytical model for the dynamic response of blast-loaded arching masonry walls. (1st December 2018) - Edri, Idan E.; Yankelevsky, David Z.
Highlights: A new nonlinear SDOF model for arching masonry walls blast loads is presented. Arching masonry wall stiffness is determined from a validated static model. Mortar inelastic behavior has a pronounced effect on the dynamic response. Calculations of the dynamic thrust and reactions at the supports are shown. Comparisons of the model predictions with test results show very good agreement. Abstract: The dynamic response of arching masonry walls subjected to blast loads is rather complex and is accompanied by different physical aspects such as: opening/closing of cracks, unloading-reloading effects, and variable arching force magnitude and line of action with time. The longitudinal and lateral inertial forces result in a coupled in-plane/out-of-plane dynamic response. These aspects, which are not considered in present single-degree-of-freedom (SDOF) models for masonry walls simulation, enhances the wall behaviour modelling and make the dynamic analysis complex and challenging. This article presents the development procedure of a new simplified yet realistic SDOF model for the one-way dynamic response of such walls. The model is based on a new recently developed analytical model for calculating the static force-displacement relationship, which is implemented within the equation of motion. Geometric and material nonlinearities, together with loading/unloading paths in the mortar material are considered, and their effect on the dynamic response is investigated. Results of this model were compared with available test results of one-way arching URM walls exposed to blast loads. The model well predicts the maximum peak displacement as well as the overall displacement-time history within the inbound phase. New insights regarding the test specimens and the dynamic characteristics affecting the arching wall behavior are gained.